The ecological redesign of household surface cleaning sprays : a study on consumers characteristics drivers and barriers to purchasing in the Portuguese market - Novais, Rita Delgado da Rocha de Abreu (2021)
Plastic is a packaging material preferred by many companies. Its durability, strength, and low cost are just some of the factors that highlight its advantages. As a result, the demand for plastic packaging is only estimated to increase. Nevertheless, plastic packaging causes significant negative externalities on the environment, and consumers are not oblivious to these issues, demanding “greener” options. Companies, in turn, are redesigning their products’ packaging to be more ecological. This dissertation focuses on household surface cleaning sprays redesigned to a concentrated format to be diluted in a refillable spray container, in the Portuguese market. The research questions aim to understand the product’s consumer and their main purchasing drivers and barriers. Through a literature review followed by a qualitative analysis, hypotheses were created to answer these questions. A quantitative analysis was then performed to verify the hypotheses. In conclusion, regarding the consumers’ personality, the importance of equality in one's life, awareness of Earth’s limited resources, and the impactful outcome of waste-related actions increase purchasing interest. Furthermore, knowing that science without conservation is not the solution for every environmental issue, but believing in technology as the solution, increases interest. Lastly, the product’s packaging recyclability and its association with a known, private label or not, brand to assure efficacy, are purchasing drivers. In contrast, lack of product awareness, time and effort preparing the product, and expected higher prices due to the product’s innovative factor, are purchasing barriers. Additionally, product usage amount is expected to be the same as for traditional sprays.